2008
DOI: 10.1111/j.1745-7262.2008.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel UBE2B-associated polymorphisms in an azoospermic/oligozoospermic population

Abstract: By themselves, a single or double CGG deletion is unlikely to pose biologic significance. However, such deletions in this suspected promoter region are associated with increased binding affinity for SP1, and might represent one of several factors required for alteration of UBE2B gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…A recent genome-wide association study of family size and birth rates among 269 men evaluating ~250,000 SNPs revealed 41 SNPs with strong association to infertility and nine SNPs related to reduced sperm quality and function (61). The study implicated the genes USP8, UBD, EPSTI1 , and LRRC32 in male infertility, highlighting potential biomarkers (61).…”
Section: Genomic Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent genome-wide association study of family size and birth rates among 269 men evaluating ~250,000 SNPs revealed 41 SNPs with strong association to infertility and nine SNPs related to reduced sperm quality and function (61). The study implicated the genes USP8, UBD, EPSTI1 , and LRRC32 in male infertility, highlighting potential biomarkers (61).…”
Section: Genomic Biomarkersmentioning
confidence: 99%
“…A recent genome-wide association study of family size and birth rates among 269 men evaluating ~250,000 SNPs revealed 41 SNPs with strong association to infertility and nine SNPs related to reduced sperm quality and function (61). The study implicated the genes USP8, UBD, EPSTI1 , and LRRC32 in male infertility, highlighting potential biomarkers (61). Other genes with SNPs associated in male fertility include: PDE3A, EFCAB4B, COBL, ATP8A1, MASP1, PROK2 (62), AHRR (46, 47), MTHFR (5860) and UBE2B , a homolog of the DNA repair gene rad6 in mice, which results in male infertility when knocked out (61).…”
Section: Genomic Biomarkersmentioning
confidence: 99%
“…Therefore, they proposed that UBE2B might be involved in sperm production in humans. However, Huang et al (2008) have demonstrated that the allelic frequency of g.-293G is 5.2% in infertile males of northern European descent and reported no statistically significant differences from the reference frequency (4.4%) published by the International HapMap Project (http://hapmap.ncbi.nlm.nih.gov/), although it is lower than the previously reported frequency of 20% from the National Center for Biotechnology Information (http://www.ncbi.nlm.nih.gov/SNP/).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis, including promoter studies, have been conducted on human and mouse spermatogenesis. For example, polymorphisms in the human UBE2B gene are associated with the human azoospermic/oligozoospermic population [9,10]. It is suspected that more genes play critical roles in human spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%